Improved oil recovery by application of ultrasonic stimulated waterflooding - Mohammadain, Erfan (Penerbit UTM Press, 2011)
Application of ultrasonic waves as an unconventional enhanced oil recovery method has been a point of interest for some decades. However, despite number of researches on ultrasonic applications, the influencing mechanisms are not fully comprehended. The aim of this study is to experimentally investigate the effects of ultrasonic waves on recovery of waterflooding and to discuss the mechanisms involved. Series of straight (normal) and ultrasonic stimulated waterflooding experiments were conducted on a long unconsolidated sand pack using ultrasonic transducers. Kerosene, vaseline and engine oil were used as non wet phase in the system. Moreover, a series of supplementary experiments were conducted using ultrasonic bath in order to enhance the understanding about contributing mechanisms. 2–16% increase in the recovery of waterflooding was observed. Emulsification, viscosity reduction and cavitation were identified as contributing mechanisms.